The Lost Fish of Turkey: A Recent History of Disappeared Species and Commercial Fishery Extinctions for the Turkish Marmara and Black Seas - Ulman, Aylin; Zengin, Mustafa; Demirel, Nazli; Pauly, Daniel (Frontiers in Marine Science, 2020)
A timeline of commercial fisheries extinctions and a list of threatened or extirpated marine species are presented to document the rapidly declining abundance of marine resources in the Turkish part of the Black Sea and Marmara Sea. Turkish nationally reported fisheries data were compared over a 50-year period from 1967 (the first year data were spatially allocated) to 2016 to assess which species are now extirpated (i.e., earlier present, and now absent from reported catch data), and which species have become commercially extinct (i.e., whose catch declined by 80.0 - 99.9%). The size of bony fish caught in Turkish waters has also strongly declined. Other important taxa, specifically big sharks and mammals, not covered by fisheries statistics, or currently under protection, but also exhibiting worrisome declining trends, are discussed based on accounts based on peer-reviewed and grey literature and personal accounts from local scientists and fishers. Overall, the Turkish parts of the Black Sea lost 17 extirpated species and 17 commercially extinct marine species, while the Sea of Marmara lost 19 extirpated species and 22 commercially extinct species. This study commemorates the many lost species of the Black and Marmara Seas, and may be seen as a warning call to prevent dozens of others species to be lost. We urge the Turkish authorities to take measures to effectively reduce fishing effort and thus to allow for a natural rebuilding of what remains of the fish stocks exploited by commercial fisheries.